2017
DOI: 10.1021/acs.langmuir.7b02634
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Interparticle Distance within Dimers in Solution Measured by Light Scattering

Abstract: We demonstrate a novel approach to quantify the interparticle distance in colloidal dimers using Mie scattering. The interparticle distance is varied in a controlled way by changing the ionic strength of the solution and the magnetic attraction between the particles. The measured scaling behavior is interpreted using an energy–distance model that includes the repulsive electrostatic and attractive magnetic interactions. The center-to-center distances of particles with a 525 nm radius can be determined with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…20). Within the magnetic dimers, it is not trivial to model the surface-to-surface distance of the particles, because the interparticle distance results from the sum of several interparticle forces with different signs and length ranges, for example the Hamaker force, electrostatic forces, the magnetic force, entropic forces such as the hydrophobic effect and steric repulsion, and the depletion force; in addition, surface roughness can be important (28). To enable a calculation starting from the basic force equations, one would need to know the underlying particle parameters with high precision, which is not the case for the particles used in this study.…”
Section: Aggregation Rate Simulationsmentioning
confidence: 99%
“…20). Within the magnetic dimers, it is not trivial to model the surface-to-surface distance of the particles, because the interparticle distance results from the sum of several interparticle forces with different signs and length ranges, for example the Hamaker force, electrostatic forces, the magnetic force, entropic forces such as the hydrophobic effect and steric repulsion, and the depletion force; in addition, surface roughness can be important (28). To enable a calculation starting from the basic force equations, one would need to know the underlying particle parameters with high precision, which is not the case for the particles used in this study.…”
Section: Aggregation Rate Simulationsmentioning
confidence: 99%
“…38 With a detection angle of the scattered light at 90 degrees, Ranzoni et al 43 demonstrated that the concentration of PSA in undiluted blood plasma could be measured in the low picomolar range, by recording the amplitude of the 2f signal (at twice the driving frequency). Vliembergen et al 124,125 have extended the optical detection method by analyzing the rotation-angle dependent scattering signals. Sharp peaks in the spectrum allowed them to measure nanometer-scale inter-particle distances within the clusters.…”
Section: Biomarker Detection and Concentration Determinationmentioning
confidence: 99%